MONITORING HEAVY METALS, CATIONS AND ANIONS LEVELS ANDITS POSSIBLE HEALTH RISKS IN TIGRIS RIVER AT BAGHDADREGION - Abdul-Kareem, Bahaa; Rabee, Adel; Al-Fatlawy, Yaaroub (Iraqi Journal of Science, 2024)
Various heavy metals, cations and anions of the Tigris River water in Baghdad regionwere studied during the winter, spring, summer and autumn of 2009, for 4 samplingsites. In the present investigation the levels of studied heavy metals, cations and anionswere found in the range of (0.011-0.333 mg/L) for As, in the water samples(undetectable-0.0043 mg/L) for Sb,( 0.011-0.080 mg/L) for Ti, (0.150-0.730 mg/L) forV, (0.01-1.06 mg/L) for Fe, (0.1-0.4 mg/L) for Zn, (0.011-0.15 mg/L) for Pb, (0.01-0.05mg/L) for Cd, (0.01-0.04 mg/L) for Ni, (50-290 mg/L) for Ca, (97-270 mg/L) for Mg,(0.65-1.74 mg/L) for K, (11-38.33) for Na, (35-113 mg/L) for Cl, (150-256 mg/L) forHCO3, (96-479 mg/L) for SO4, (0.93-3.9 mg/L) for NO3 and (undetectable - 0.360 mg/L)for PO4. Some parameters like As, V, Fe, Pb, Cd, Mg and SO4 are higher than thevalues recommended in international and Iraqi criteria for drinking water, while the restions were within the acceptable limits. In general, the results confirmed that Tigris Riverat study area is slightly contaminated with some hazardous heavy metals especially Pband Cd which have ability to biological concentration in organisms bodies and thatmight affect human health as well as the health of the ecosystem.